STORYTELLING AS AN EFFECTIVE METHOD IN TEACHING ENGLISH TO CHILDREN - Omonova Maftuna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article explores storytelling as an effective method in teaching English to children. Storytelling has long been recognized as a powerful educational tool that helps young learners develop language skills, imagination, and emotional understanding. The study focuses on how storytelling supports vocabulary development, listening comprehension, and communicative competence in English language learning. By analyzing modern pedagogical approaches and classroom practices, the research highlights the benefits of integrating storytelling into language instruction for children. The findings indicate that storytelling creates an engaging learning environment, motivates students, and enhances language acquisition through meaningful context. The study emphasizes the importance of creative teaching strategies and demonstrates that storytelling contributes significantly to improving children’s interest and participation in English language learning.